The Effect of Anabasis articulata Stems Extract on Lowering Intraocular Pressure in the Glaucoma Rat Model(Conference Paper )# - Abdulsahib, Waleed K. (Iraqi Journal of Pharmaceutical Sciences, 2022)
High intraocular pressure (IOP) is a recognized risk factor for glaucoma and optic nerve injury, and it is one of the primary causes of vision loss globally. Anabasis articulata (AA) is a desert plant found in Iraq. The extract of AA is used to cure diabetes, fever, eczema, and kidney infections. The aim of the study is to evaluate the antioxidant effect of methanol extract of AA on intraocular pressure in the glaucoma rat model. Forty-two rats were allocated into seven groups, each with six animals:: group 1 (normal), group 2 (control), in which animals were induced to have elevated IOP by betamethasone suspension injection, groups 3,4 and 5 for evaluating the effect of 50,100 and 150 mg/kg/day of the tested extract, respectively, and the remaining two groups (group 6 and 7) for evaluating oral acetazolamide and topical timolol 0.5% respectively. Betamethasone was used for the induction. Measure the IOP every 2 days for 2 weeks. The daily dose of AA extract (50 mg/kg/day) for 6 days significantly reduces intraocular pressure (p ? 0.05), from (34.23± 0.58) to (32.83± 1.38) mmHg when compared with the control group. In group 4, IOP decreased significantly from (35.5±1.37) to (31.35±0.40) mmHg (p ? 0.05) after 1 week of treatment. In group 5, the significant (p? 0.001) IOP reduction from (35.66±0.39) to (31.88±0.74) mmHg started on day 6 and continued until the end of the experiment, reaching (24.53±0.53) mmHg (p? 0.001). The antioxidant and anti-angiogenic properties of AA make it a promising adjuvant treatment for glaucoma.